Rituximab-Induced Coronary Vasospasm - Linda Lee; Vishal Kukreti (Case Reports in Hematology)
Rituximab has improved the treatment of B-cell non-Hodgkin lymphomas. While it is generally well tolerated, serious adverse effects including infusion reactions with hemodynamic compromise and cardiac arrhythmias or ischemia are possible. We report a case of coronary vasospasm occurring during a rituximab infusion in a patient with minimal tumour burden and who had no cardiac risk factors. This case highlights that determination of the cause of ischemia is important and may identify some patients who can be successfully rechallenged.